Two-dimensional analysis method of bonding stress at steel-bamboo interface. (March 2022) - Li, Yushun; Zhang, Jialiang; Zhang, Xiaocun; Tong, Keting; Shan, Qifeng
Abstract: The steel-bamboo composite structure is a novel composite system in which structural components are composed of laminated bamboo panel and cold-formed thin-walled steel using structural adhesive. Therefore, the study of the interaction and bonding failure mechanism between bamboo panel, steel and adhesive layer is the prerequisite for ensuring that the system can give full play to the advantages of materials. In this paper, a two-dimensional mechanical model for calculating the interface stress between steel and bamboo is proposed. The theoretical solution not only satisfies the boundary condition of zero bonding shear stress at the end of the adhesive layer, but also solves the normal peeling stress, which cannot be obtained in one-dimensional theory. The maximum value of equivalent stress determined in two-dimensional analysis method agrees well with one-dimensional solution with an average error of 8.92%, which proves that the two-dimensional analysis method is feasible and reliable.